أثر أسعار البترول على بعض المتغيرات الاقتصادية الكلية -حالة الجزائر- - بن قدور, علي; كردودي, سهام; السبتي, وسيلة (Université de M'sila, 2016)
The study of the price of oil in Algeria, inspired by the importance of their role in guiding policies and programs idealism that would at least reduce the negative residue of changes in price, and in order to reach the goals of this research was to Zuma's attempt to study the effect of changes in oil prices on some macro-economic variables , where he showed the results of this research and through models applied to the price of oil in Algeria for many external factors outside the control of the economic variables in addition to speculation and political factors, movements and regional security.
Keywords: Oil prices, petroleum policy, the joint integration, preprocessing, causality.